Analysis of Sea Surface Temperature and Its Correlation with Changes in Coastlines Using Landsat 8 Satellite Image Data (Case Study: Ujung Pangkah Gresik) - Hendrata Wibisana; Zetta R. Kamandang; Siti Zainab (Future Science)
Changes in the coastline are a natural phenomenon that often occurs on various coasts where this event has a further effect in the form of sedimentation and erosion along the coast. As a result of this phenomenon, the coast is said to be dynamic towards the various changes that occur, and one of them is the change in sea surface temperature. The purpose of this research is to find a correlation of changes in sea surface temperature to changes in the existing shoreline on the coast of Ujung Pangkah Gresik in addition to calculating the speed of change of the coastline. The method used is the use of remote sensing technology to analyze sea surface temperature and geographic information systems to analyze changes in coastlines. The results obtained from this study are changes in sea surface temperature statistically affect changes in coastlines with an error rate of 5% at the 20 measured observation points. The model used in sea surface temperature is a linear model with an R-value of 0.783, and the change in the coastline at Ujung Pangkah Gresik is 153 meters per year measured between 2019 and 2020. The conclusion obtained from this study is that the increase in sea surface temperature will affect climate change on the coast and will ultimately affect changes in the coastline.